The Influence of Budget Planning, Cost Management, Internal Control, Cash Management, and Financial Analysis on MSME Performance - Nurlaelah, Nurlaelah; Siti Mudawanah (Edupedia Publisher, 2026)
Purpose - Micro-enterprises play a strategic role in regional economic development, including in Banten Province. However, many micro-enterprises still face weaknesses in financial management, which negatively affect their business performance. The provision of micro-enterprise loans by financial institutions has not been sufficiently accompanied by improvements in borrowers’ financial planning and control capabilities. This study aims to analyze the influence of budget planning, cost management, internal control, cash management, and financial analysis on the business performance of micro-enterprise loan recipients in Banten Province. Methodology - This study adopts a quantitative research design using a survey method. Primary data were collected through structured questionnaires distributed to micro-enterprise loan recipients in Banten Province. A total of 140 valid responses were obtained from MSME actors. The collected data were analyzed using SPSS version 30, employing descriptive statistics and multiple linear regression analysis to examine both partial and simultaneous effects of financial management variables on MSME performance. Findings – The results show that budget planning, cost management, internal control, cash management, and financial analysis have a fairly high correlation with business performance and exert a significant positive influence, both partially and simultaneously. The model explains 58.3% of the variance in MSME performance, indicating that strengthening financial management capabilities plays a substantial role in improving sustainable business performance. These findings imply that financial management practices are critical determinants of micro-enterprise success. Novelty – This study provides empirical evidence on the combined impact of multiple financial management dimensions on the performance of micro-enterprise loan recipients at a regional level, specifically in Banten Province. Significance – The findings benefit micro-entrepreneurs, financial institutions, and policymakers by highlighting the importance of integrating financial management capacity-building programs with micro-enterprise lending schemes.